Pathway of Sinological Studies of Early Spanish Dominican Missionaries - Xiao, Yin (Sinología hispánica. China Studies Review, 2026)
Based on the Chinese writings and letters of Dominican priests such as Juan Cobo, Miguel Benavides, Domingo de Nieva and Tomás Mayor and other materials, this article analyses the sinological level of these authors and their attitudes towards Chinese culture, investigating the process of their learning Chinese language and culture in Manila (Philippines) and the materials on which they relied. It attempts to clarify the main purposes, methods, means, achievements of their Sinological studies, as well as how they applied their sinological knowledge in their missionary works. The present work also situates their sinological studies in the specific historical and geographical background, in order to understand and objectively evaluate the Hispanic missionary sinology from the late sixteenth to the early seventeenth century.